2018
DOI: 10.1539/joh.2018-0050-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese Workplace PERMA-Profiler: A validation study among Japanese workers

Abstract: Objectives: Although well-being at work is important for occupational health, multi-dimensional workplace well-being measures do not exist for Japanese workers. The purpose of this study was to investigate the validity of the Japanese version of the Workplace PERMA-Profiler. Methods: Japanese workers completed online surveys at baseline (N = 310) and 1 month later (N = 100). The Workplace PERMA-Profiler was translated according to international guidelines. Job and life satisfaction, work engagement, psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…The CFA indicated that the 5-factor PERMA model had a marginally acceptable fit [χ 2 (80) = 383.04, CFI = 0.909, TLI = 0.881, RMSEA = 0.110, SRMR = 0.054], rather than completely supporting the 5-factor structure. However, the original PERMA-Profiler (CFI =0.894, TLI =0.864, RMSEA =0.107) and Japanese Workplace PERMA-Profiler (CFI = 0.892, TLI = 0.858, RMSEA = 0.105) had similar values [1027]. This marginally acceptable fit suggests that the 5-factor PERMA model might not be the most appropriate model measuring workplace well-being or the items might not adequately separate the 5 factors in the Korean workplace context.…”
Section: Discussionmentioning
confidence: 99%
“…The CFA indicated that the 5-factor PERMA model had a marginally acceptable fit [χ 2 (80) = 383.04, CFI = 0.909, TLI = 0.881, RMSEA = 0.110, SRMR = 0.054], rather than completely supporting the 5-factor structure. However, the original PERMA-Profiler (CFI =0.894, TLI =0.864, RMSEA =0.107) and Japanese Workplace PERMA-Profiler (CFI = 0.892, TLI = 0.858, RMSEA = 0.105) had similar values [1027]. This marginally acceptable fit suggests that the 5-factor PERMA model might not be the most appropriate model measuring workplace well-being or the items might not adequately separate the 5 factors in the Korean workplace context.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, future studies could use the SEIC short form to determine whether aspects of personality as independent variables (Dewaele, 2012) are responsible for fostering greater or lesser engagement with host-nationals or interacting partners in intercultural learning programs. Investigators of the role of SEIC as a factor in professional self-efficacy and positive psychology might also meaningfully apply the tool with PERMA profiler and framework for the workplace (Watanabe et al, 2018). In sum, while more validation remains to be done, the present study offers degrees of internal and external validity for the domain of interest to SEIC.…”
Section: Limitations and Future Directionsmentioning
confidence: 85%
“…Overall, at present, our findings indicate some potential for the SEIC to identify individuals who might possess higher baseline IES dimensions of Continuous Learning and Interpersonal Engagement, which are hypothesized to map on to traits such as openness to, respect for, and curiosity about other cultures, and are widely believed to be conducive to developing intercultural competence (Deardorff, 2006). Future research perhaps using goal-related theories like self-determination theory (Lee and Bong, 2019;McEown and Oga-Baldwin, 2019) more conventionally measured positive psychology constructs (Dewaele et al, 2019) plausibly extending to authentic personality for students (Wood et al, 2008) or PERMA in the workplace (Watanabe et al, 2018) for professionals might be useful directions to further investigate these relationships.…”
Section: Self-efficacy In Intercultural Communication As Competency Imentioning
confidence: 99%
“…A question taken from the PERMA-Profiler [41] was asked, "Taking all things together, how happy would you say you are?" The PERMA-Profiler is the measure of well-being based on Seligman's theory [42] and its reliability and validity are confirmed both in English and Japanese versions [43]. The item was rated on an 11-point Likert scale (0 = not at all, 10 = completely), and a higher score indicated higher happiness.…”
Section: Subjective Well-beingmentioning
confidence: 99%